Functional Characterization of a Novel Heterozygous Mutation in the Glucokinase Gene That Causes MODY2 in Chinese Pedigrees - Jiang, Feng; Yan, Jing; Zhang, Rong; Ma, Xiaojing; Bao, Yuqian; Gu, Yujuan; Hu, Cheng (Frontiers in Endocrinology, 2021)
Background Glucokinase (GCK) plays a central role in glucose regulation. The heterozygous mutations of GCK can cause a monogenic form of diabetes, maturity-onset diabetes of the young (MODY) directly. In our study, we aimed to explore the mechanism of the novel mutation GCK p.Ala259Thr leading to glucokinase deficiency and hyperglycemia. Methods Thirty early-onset diabetes pedigrees were referred to whole exome sequencing for novel mutations identification. Purified wild-type and mutant GCK proteins were obtained from E.coli systems and then subjected to the kinetic and thermal stability analysis to test the effects on GCK activity. Results One novel missense mutation GCK p.Ala259Thr was identified and co-segregated with diabetes in a Chinese MODY2 pedigree. The kinetic analysis showed that this mutation result in a decreased affinity and catalytic capability for glucose. The thermal stability analysis also indicated that the mutant protein presented dramatically decreased activity at the same temperature. Conclusion Our study firstly identified a novel MODY2 mutation p.Ala259Thr in Chinese diabetes pedigrees. The kinetic and thermal stability analysis confirmed that this mutation caused hyperglycemia through severely damaging the enzyme activities and protein stability.